The improvement of livestock production in Nigeria through breeding - Ngere, L.O. (1975)
There was an obvious need for improved livestock production in Nigeria. This paper discusses the improvement of genetic potential of livestock for favoured production traits. Livestock breeding policies and programmes are necessary for the successfull implementation of the national development plan.